The relationship of secondary school library use and library anxiety among UP Diliman freshmen students - Legaspi, Connie Lea C. (2007)
This study investigates the relationship of secondary school library use - frequency of high school library use and reason/s for using the high school library and library anxiety, in terms of the four factors, namely: situational factors, social factors, psychological factors, and technical factors. Participants were 357 UP Diliman freshmen. Findings revealed that UP Diliman freshmen have high levels of anxiety across the three factors: situational, social and technical factors. In terms of psychological factors, students have a fair level of anxiety. In all, it was found that high level of library anxiety exists among UP Diliman freshmen.